Trajetos de sentidos sobre a mudança climática na discursivização da revista Superinteressante (1995-2015) - Winch, Rafael Rangel (2017)
In a context marked by the environmental crisis, climate change emerges as a multidimensional problem, gathering scientific, political, economic, sociocultural factors and implications, among other types. Besides their physical properties, climate phenomenon is also constructed discursively, largely, by journalism. Based on this, the research aims to understand how the discourse on climate change is constructed in magazine Superinteressante, by Abril Company, between 1995 and 2015. The study discusses central aspects related to climate change, highlighting some their historical elements. It also reflects on journalistic coverage of climate change, magazine journalism, and relation between journalism and science. In order to interpret the meanings about climate change in Superinteressante, we use theoretical-methodological French Discourse Analysis. The corpus is formed by 343 discursive sequences, taken from 21 texts, and that are inserted in ten Paraphrastic Networks. These networks, in turn, are encompassed in four Discursive Formations that represent forms of understanding climate change from specific domains, they are: (DF1) Climate change has undesirable effects; (DF2) Climate change is about human action; (DF3) Climate change is a controversial issue; (DF4) Climate change is an unequal problem. Discursive listening points to a significant predominance of (DF1) and, soon after, of (DF2), which shows that the meanings most frequently reiterated by magazine concern negative consequences and human dimensions associated with the problem. In addition, we verified that Superinteressante not just reiterates discourses about the various dimensions of phenomenon, but also updates them over the years.